Use of Boey’s score in peptic perforation disease in the Nepalese population: a prospective observational study - Koirala, Rabin; Pant, Paras; Acharya, Nikhil; Rajbhandary, Asish (Journal of Society of Surgeons of Nepal, 2019)
Introduction: Peptic ulcer perforation carries high mortality and morbidity. Boey’s score is shown to be a simple scoring system to help predict morbidity and mortality. This is a prospective observational study to evaluate the applicability of Boey’s score in predicting mortality and morbidity in Nepalese patients. Methods: This study was conducted in the Dept. of Surgery, Nepal Medical College and Teaching Hospital (NMCTH), Attarkhel, Jorpati between 1st of July 2012 to 30th June 2019 over a period of 7 years. This was a prospective observational study. All patients who underwent laparotomy for suspected peptic ulcer perforation peritonitis were included in the study. Results: Fourty-seven patients were included in the study. Male patients outnumbered females by a ratio of almost 4:1. Eighteen (38%) patients had Boey’s score of 1, and 7 (15 %) patients had a Boey’s score of 3. Overall postoperative mortality was 7 (15%). Boey’s score predicted morbidity and mortality with a p-value of <0.01. The length of hospital stay was also more in patients with a higher score and it was statistically significant. Conclusions: Boey’s score is both easy and effective in predicting postoperative morbidity, mortality and length of hospital stay.